2022
DOI: 10.1111/ecc.13672
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular carcinoma and its impact on quality of life: A review of the qualitative literature

Abstract: Introduction: Hepatocellular carcinoma (HCC) carries significant burden of disease, with high mortality rates and poor prognosis. It is therefore important to consider quality of life (QoL) for patients with HCC. Quantitative research assesses HCC and QoL via standardised measurement tools, but these do not capture the full scope of patient experiences. This review examines the body of qualitative research on this topic, to develop a comprehensive understanding of QoL for this population.Methods: Medline, EMBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…HCC has a profound negative impact on patients' QoL (27). In addition, the fear of recurrence, especially after surgery or liver transplantation, also seriously affects this (28).…”
Section: Discussionmentioning
confidence: 99%
“…HCC has a profound negative impact on patients' QoL (27). In addition, the fear of recurrence, especially after surgery or liver transplantation, also seriously affects this (28).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the general public's representation of liver disease often includes the idea that a patient's disease was caused by alcohol consumption, which may be true or not [ 32 , 35 , 36 ]. As a consequence, patients with liver diseases may experience stigma and a strong feelings of shame [ 37 , 38 ]. Several studies showed that stigma can cause considerable distress in liver cancer patients [ 37 , 38 ], increasing the risk of depression and anxiety [ 39 , 40 ] and decreasing patients' quality of life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, patients with liver diseases may experience stigma and a strong feelings of shame [ 37 , 38 ]. Several studies showed that stigma can cause considerable distress in liver cancer patients [ 37 , 38 ], increasing the risk of depression and anxiety [ 39 , 40 ] and decreasing patients' quality of life [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, QoL comprehends not only clinical problems but also psychological, social and financial disease-related burdens: if QoL decreases, and liver function decompensation occurs, an upgrade of supportive treatment strategies is necessary. QoL should be an essential parameter for clinical outcomes in future prospective trials, particularly in those attempting the development of new therapeutic associations ( 12 ). We also strongly agree with SITC guideline on the institution of a more patient-centered medical environment, based on comprehensive counseling and education about expected or unexpected effects from treatment, and involvement in support groups.…”
mentioning
confidence: 99%